Disorder in the court : Language use by “Gray Area” pro per defendants - Greenlee, Mel (Language and Law / Linguagem e Direito, 2017)
In California, criminal defendants may serve as their own advocates at trial, even in capital cases, if the trial judge deems them mentally competent to do so. Nevertheless, the extent to which some pro per litigants are able to understand and follow the rituals of the courtroom may be seriously affected by mental symptoms. This paper examines courtroom interactions in a small number of cases where such defendants attempted to fulfill a dual role, reviewing their expressions of legal theories, questioning, and attention to guidance by the trial judge – all of which features would be in stark contrast to the prosecution’s expertise, and all of which would be arguably affected by mental illness. While the defendants vary in control of legal lexicon and courtroom formalities, close analysis shows that they tend to share diculties in self-monitoring, pragmatic perspective and coherence – decits which may confuse or perplex other courtroom players and doom their eorts at advocating for themselves.